2024
DOI: 10.1002/jso.27585
|View full text |Cite
|
Sign up to set email alerts
|

Internal hemipelvectomy: A single institution's learning curve and longitudinal experience

Rajko S. Vucicevic,
Athan G. Zavras,
Michael P. Fice
et al.

Abstract: Background and ObjectivesWide margin resection for pelvic tumors via internal hemipelvectomy is among the most technically challenging procedures in orthopedic oncology. As such, surgeon experience and technique invariably affect patient outcomes. The aim of this clinical study was to assess how an individual surgeon's experiences and advancements in technology and techniques in the treatment of internal hemipelvectomy have impacted patient outcomes at our institution.MethodsThis study retrospectively examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…As precision and innovation remain paramount in orthopaedic oncology, collaborative, multidisciplinary research endeavors are essential to unravel the complexities of guide design and improve surgical outcomes for patients with pelvic tumors. c This retrospective study of 72 pelvic malignant tumors demonstrated the transition to utilizing more 3D navigation and customized 3D cutting guides, which resulted in lower perioperative bleeding in the patient-specific instrumentation group [9].…”
Section: How Do We Get There?mentioning
confidence: 95%
See 1 more Smart Citation
“…As precision and innovation remain paramount in orthopaedic oncology, collaborative, multidisciplinary research endeavors are essential to unravel the complexities of guide design and improve surgical outcomes for patients with pelvic tumors. c This retrospective study of 72 pelvic malignant tumors demonstrated the transition to utilizing more 3D navigation and customized 3D cutting guides, which resulted in lower perioperative bleeding in the patient-specific instrumentation group [9].…”
Section: How Do We Get There?mentioning
confidence: 95%
“…Some articles suggest increased radiological accuracy and alignment, whereas others show no improvement in accuracy. Often the results do not demonstrate any differences in functional or clinical outcomes [1,2,7,9]. However, the question of whether custom guides have a role to play in the resection of bone tumors is more controversial.…”
mentioning
confidence: 99%